2014
DOI: 10.1111/bph.12659
|View full text |Cite
|
Sign up to set email alerts
|

ABT‐263 enhances sorafenib‐induced apoptosis associated with Akt activity and the expression of Bax and p21(CIP1/WAF1) in human cancer cells

Abstract: BACKGROUND AND PURPOSESorafenib, a potent inhibitor that targets several kinases associated with tumourigenesis and cell survival, has been approved for clinical treatment as a single agent. However, combining sorafenib with other agents improves its anti-tumour efficacy in various preclinical tumour models. ABT-263, a second-generation BH3 mimic, binds to the anti-apoptotic family members Bcl-2, Bcl-xL and Bcl-w, and has been demonstrated to enhance TNFSF10 (TRAIL)-induced apoptosis in human hepatocarcinoma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 50 publications
4
13
0
Order By: Relevance
“…Akt activates the mTOR signaling pathway (37) and represses p21, as well as Bax, to enhance cell proliferation preventing apoptosis (38,39). Therefore, Akt downregulation by PTEN in ES cells induced the upregulation of p21 and Bax, which might have resulted in cell cycle inhibition and apoptosis in ES cells.…”
Section: Discussionmentioning
confidence: 99%
“…Akt activates the mTOR signaling pathway (37) and represses p21, as well as Bax, to enhance cell proliferation preventing apoptosis (38,39). Therefore, Akt downregulation by PTEN in ES cells induced the upregulation of p21 and Bax, which might have resulted in cell cycle inhibition and apoptosis in ES cells.…”
Section: Discussionmentioning
confidence: 99%
“…An empty vector pHAGE.puro plasmid was kindly provided by Dr Zan Huang (College of Life Sciences, Wuhan University, China), and pHAGE.puro-p21 plasmid was obtained from our laboratory (Li et al, 2014a). The empty vector p-USE and p-USE-CA-Akt plasmids were obtained from Upstate Biotechnology (Lake Placid, NY, USA).…”
Section: Plasmids and Transfectionsmentioning
confidence: 99%
“…p21 expression is involved in apoptosis induced by combination treatment p21 CIP1/WAF1 , a potent inhibitor of cyclin-dependent kinase (CDK), has been identified as a key element in chemotherapeutic agent-and DNA-damaging agent-induced apoptosis (Stivala et al, 2012;Lee et al, 2013a). We previously reported that p21 is a critical regulator of combination treatmentinduced apoptosis (Li et al, 2014a). Thus, we next examined whether p21 expression was related to the sensitivity of cancer cells to apoptosis induced by tetrandrine/chloroquine…”
Section: Inhibition Of Tetrandrine-induced Cell Autophagy Causes Cellmentioning
confidence: 99%
“…Although liver transplantation, surgery, and interventional radiology, Sorafenib (or Nexavar) as a receptor tyrosine kinase inhibitor has been applied to over half of the patients with HCC for years, recent 1 year relative survival rate is less than 50% (Fukuda et al, 2014;Graf et al, 2014). Because the side effects of Sorafenib are known severe with erythema multifomre, hand-foot syndrome (Yang et al, 2008), diarrhea, and vomiting and nausea (Berk et al, 2013), recently, herbal drugs (Hu et al, 2013) or natural compounds (Huynh et al, 2014) are attractive for the prevention or treatment for HCC alone or by combination therapy with Sorafenib (Cao et al, 2011;Hu et al, 2013;Huynh et al, 2014;Li et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%